Analisis Dampak Program Pengelolaan Penyakit Kronis (Prolanis) Dalam Meningkatkan Outcome Klinis Pasien Diabetes Melitus Tipe 2 Di Puskesmas Jakarta, Indonesia - Reise Manninda; Yusi Anggriani; Astrid Kartika Sari (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Prolanis is a Chronic Disease Management Program under the Indonesian National Health Insurance for promoting and preventing chronic disease. Main activities of Prolanis program are disease control and counseling, scheduled education, scheduled exercise, participant’s remainder, and home visit. The aim of this study was to evaluate the impact of prolanis on the clinical outcome in type 2 Diabetes Mellitus (DM) patients. An observational retrospective study was evaluated for 12 months. Data was collected from medical record. 426 patients from five primary health care center in Jakarta was selected by simple random sampling and divided into prolanis and non-prolanis groups. The indicators were the difference of clinical outcome between prolanis and non-prolanis patients was analyzed using Mann-Whitney test; the correlation of adherence with clinical outcome was analyzed using Chi-Square test.The results showed that prolanis patients had a significant improvement in Fasting Blood Glucose (FBG) compared with non-prolanis patients (P<0.05). The adherence of prolanis patients showed a significant improvement on FBG (124 patients-58.2%). Patients with nonadherence had lower improvement on FBG, the improvement was observed only at 16 patients (7.5%) and 60 patients (28.17%) was poor FBG. Prolanis is an effective program to improve the clinical outcome of DM patients.